Wide bandwidth lasing randomly assembled ZnS/ZnO biaxial nanobelt heterostructures - Yan, J. (2011)
Wide-bandwidth random lasing action is observed from the randomly assembled ZnS/ZnO biaxial nanobelt heterostructures under optical excitation. This is because optical gain at ultraviolet regime can be obtained from the near-band-edge radiative recombination of ZnS and ZnO. Surface defects related radiative recombination centers of ZnS and ZnO nanostructures also contribute to the visible optical gain. Hence, a broadband optical gain is obtained from the ZnS/ZnO biaxial nanobelt heterostructures. Moreover, a wide bandwidth coherent optical feedback can be achieved from the randomly assembled biaxial nanobelts due to high refractive index contrast between the nanobelts and air.